What is the remainder when 1 2 0 1 3 + 2 2 0 1 3 + ⋯ + 2 0 1 2 2 0 1 3 + 2 0 1 3 2 0 1 3 is divided by 2 0 1 4 ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Will you please explain me the last step? How did you multiply the mod bases?
Log in to reply
1 0 0 7 2 0 1 3 ≡ 1 (mod 2) 1 0 0 7 2 0 1 3 ≡ 0 (mod 1007) According to the Chinese Remainder Theorem, 1 0 0 7 2 0 1 3 ≡ 1 0 0 7 (mod 2014)
Can you explain the first step please?
Log in to reply
It's just basically telling you that 1 2 0 1 3 and 2 0 1 3 2 0 1 3 are opposites m o d 2 0 1 4 . So are 2 2 0 1 3 and 2 0 1 2 2 0 1 3 , and so on, so everything cancels out except 1 0 0 7 2 0 1 3 .
A^N + B^N is completely divisible by A+B when powers r odd, here if we combine the extremes we get the required pattern... Hence the remainder should b zero (1^2013 + 2013^2013 + 2^2013 + 2012^2013 +..... ) /2014
Log in to reply
By using this we can get up till 1006^2013and1008^2013 but 1007^2013 do not get cancelled
got all but 1007^2013 mm , can u explain this step ? is it theorm ?
Log in to reply
1007^2=1(mod 2014) > (1007)^2012=1 mod(2014) and 1007=1007(mod 2014). hence (1007)^2013=1007(mod 2014). (note, here "=" has been used in place of "congruent to"
What. Is. Mod
Log in to reply
"mod" is short for "modulus". When we carry out operations under a natural number modulus, we only care about the remainder after you divide by that modulus. Basically, we are splitting up all integers into equivalency classes that are represented by the remainder after division. For instance, we could say "25 = 4 (mod 7)", because 7 goes into 25 a certain number of times (3 times, but we don't care about that), with a remainder of 4 (which we DO care about). Similarly, we could say that "23 = 3 (mod 4)", because 23 = 5×4 + 3 = k×modulus + remainder. We could also say that "27 = 3 (mod 4)" for the same reason. By that, every fourth number starting with 3 (in both the negative and positive directions) is equivalent to 3 (mod 4); i.e. ...., -9, -5, -1, 3, 7, 11,... are all the same as 3 in the modulus of 4.
Hope that helps. :)
WolframAlpha code
mod(sum(n^2013,n=1 to 2013),2014)
1007
I did the same cancellation as you did; however, I had a different approach for the last one. I was thinking about ways to simplify 1007^2013 mod 2014 and then I realized it is equivalent to -1007^2013 mod 2014 That means it's mod m = 2014 - m. Solving for m gives 1007. In general this works for any modulus that is twice and odd applied to that odd. For example, 3^5 mod 6 is 3.
Log in to reply
Could you explain how you have simplified it?
Alternatively, note that x = 1 0 0 7 2 0 1 3 ≡ ( − 1 0 0 7 ) 2 0 1 3 ≡ − ( 1 0 0 7 2 0 1 3 ) = − x , so 2 x ≡ 0 ⟹ x ≡ 0 , 1 0 0 7 (mod 2014) .
How did you get 1007^2013 is congruent to 1 modulo 2? I can't figure out an easy way to do that..
Log in to reply
Note that an odd number times itself is still odd. This always works, so 1007^13 is odd.
Please explain the second step.
@AnuRadha , that's just a parity check - an odd number divided by 2 leaves a remainder 1.
@Daniel Liu , I didn't understand the last step, where you ended up saying that 1007^2013 = 1007 (mod 2014)..
The meaning of the last step is, let 1007^2013 be x, x=2i+1 x=1007j Therefore x^2=2014ij+1007 Due to the fact that 1007^2=1007(mod 2014) by brute forcing ((1007)^2)^2013=1007(mod 2014) 1007^2013=1007(mod 2014)
What's 'mod'?
For n odd:
a n + b n = ( a + b ) ( a n − 1 − a n − 2 b + . . . − a b n − 2 + b n − 1 )
As 1+2013=1014, 2+2012=2014....:
1 2 0 1 3 + 2 2 0 1 3 + . . . + 2 0 1 2 2 0 1 3 + 2 0 1 3 2 0 1 3 =
1 2 0 1 3 + 2 0 1 3 2 0 1 3 + 2 2 0 1 3 + 2 0 1 2 2 0 1 3 + . . . + 1 0 0 5 2 0 1 3 + 1 0 0 8 2 0 1 3 + 1 0 0 7 2 0 1 3 ≡ 1 0 0 7 2 0 1 3 ( m o d 2 0 1 4 )
1 0 0 7 × 1 0 0 7 = 1 0 1 4 0 4 9 ≡ 1 0 0 7 ( m o d 2 0 1 4 ) ⟶ 1 0 0 7 2 0 1 3 ≡ 1 0 0 7 ( m o d 2 0 1 4 )
Same as mine
There should be 1006 instead of 1005 in row 4.
Nice explanation.
exactly what I did👍
Note that 2014 is the product of three primes 2, 19, 53, the latter two being regular. This and the fact that 2013 is odd implies that the sum of the first n 2013th powers = n^2(n+1)^2 p(n) where p(n) has rational coefficients with no factors of 19 or 53 in their denominator (regular primes do not divide Bernouilli denominators). Thus the answer is an odd multiple of 19 53=1007.
This is the smartest proof.
Sorry to say that, but this proof has a lot of flaws. As, your claim, that denominators in p(n) have no factors of 19 and 53, is wrong. In fact by Faulhaber formula, a lot of denominators are divisible by 19 or 53, for example the leading term itself, but as denominator of Bernoulli numbers is always square free there is no term whose denominator is divisible by 19^3 or 53^3, I'm not sure about squares. The theorem you mentioned about regular primes is wrong, actual theorem is concerning numerator, not denominators. And the leap you made in last line is something that I can't understand. I was trying to patch your proof, but I wasn't been able to, it's just too broken up.
Outline: Since 2 0 1 4 = 2 × 1 9 × 5 3 , we will calculate x 2 0 1 3 ( m o d 2 ) , ( m o d 1 9 ) , ( m o d 5 3 ) respectively and combine them to x 2 0 1 3 ( m o d 2 0 1 4 ) in the end.
Mod 2 Odd x give 1, even x give 0. There are 1007 odd numbers in the range 1..2013, which is odd, so ∑ x = 1 2 0 1 3 x 2 0 1 3 = 1 ( m o d 2 )
Mod 19 2 0 1 3 = 1 0 5 × 1 9 + 1 8
Taking x mod 19 ∑ x = 1 2 0 1 3 x 2 0 1 3 ≡ 1 0 5 ( ∑ x = 1 1 9 x 2 0 1 3 ) + ∑ x = 1 1 8 x 2 0 1 3 .
Observe that for odd t: ( p − a ) t ≡ ( − a ) t ≡ − a t ( m o d p ) so that for any odd power t and any odd prime p: 1 t + 2 t + . . . + ( p − 2 ) t + ( p − 1 ) t ≡ 0 .
Also observe p t ≡ 0 t ≡ 0 ( m o d p ) .
So ∑ x = 1 2 0 1 3 x 2 0 1 3 ≡ 1 0 5 × 0 + 0 ≡ 0 ( m o d 1 9 )
Mod 53 Here too, 2013 is 1 short of a multiple of 53. (Of course, because 53 is a factor of 2014.) Along the same lines we find ∑ x = 1 2 0 1 3 x 2 0 1 3 ≡ 0 ( m o d 5 3 )
Conclusion Combining the modulo information, the sum is an odd multiple of 19 and of 53, which must be 1 9 × 5 3 = 1 0 0 7 .
This was a neat problem and not as immediate as the question it was based on. Took quite a lot of observation.
by fermat's little theorem, the remainder of 1007^{2013} is 1007, when divided by 2013 also, please help.
□□□□□□□□□□□□□□□□□□□□□□↑
@Daniel liu:
Which term cancels out with
1006^2013 and 1008^2013??
Log in to reply
The 1 0 0 6 2 0 1 3 and 1 0 0 8 2 0 1 3 cancel each other out.
Problem Loading...
Note Loading...
Set Loading...
Note that k 2 0 1 3 ≡ − ( 2 0 1 4 − k ) 2 0 1 3 ( m o d 2 0 1 4 ) (this is just a fancy general way to state the next two statements and so on). Thus, 1 2 0 1 3 + 2 0 1 3 2 0 1 3 ≡ 0 ( m o d 2 0 1 4 ) 2 2 0 1 3 + 2 0 1 2 2 0 1 3 ≡ 0 ( m o d 2 0 1 4 ) and so on.
After all this cancellation, we are left with finding 1 0 0 7 2 0 1 3 ( m o d 2 0 1 4 ) . Since 1 0 0 7 2 0 1 3 ≡ 1 ( m o d 2 ) and 1 0 0 7 2 0 1 3 ≡ 0 ( m o d 1 0 0 7 ) , we conclude that 1 0 0 7 2 0 1 3 ≡ 1 0 0 7 ( m o d 2 0 1 4 )